1997
DOI: 10.1177/000992289703600804
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatnent of Nocturnal Enuresis withi Desmopressin Intranasal Spray

Abstract: The purpose of this study was to determine the efficacy and safety of long-term treatment of nocturnal enuresis with desmopressin intranasal spray. Sixty-five children with primary nocturnal enuresis with a mean age of 11.3 years (range 7-17) underwent a 2-week observation period followed by dose titration period of 1 week. Those children completely dry with desmopressin entered a randomized, placebo-controlled, double-blind phase lasting 2 weeks, followed by a 6-month open treatment. The enuretic status of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Usually, 50–85% of patients who entered the study showed at least a halving in the number of wet nights and 40–70% became almost completely dry during treatment. In five studies the patients were evaluated at regular intervals (0.5–6 months) [18–21,24]. In all studies it became evident that the efficacy of desmopressin continued or improved throughout the treatment period, indicating that the enuretics did not develop tolerance to desmopressin.…”
Section: Efficacy Of Long‐term Desmopressin Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Usually, 50–85% of patients who entered the study showed at least a halving in the number of wet nights and 40–70% became almost completely dry during treatment. In five studies the patients were evaluated at regular intervals (0.5–6 months) [18–21,24]. In all studies it became evident that the efficacy of desmopressin continued or improved throughout the treatment period, indicating that the enuretics did not develop tolerance to desmopressin.…”
Section: Efficacy Of Long‐term Desmopressin Treatmentmentioning
confidence: 99%
“…Long‐term treatment with desmopressin induced no clinically significant changes in mean values of blood chemistry (including serum sodium, potassium and osmolality) [7,15,18–22], nor significantly affected mean haematology [7,15,20,21] and urine analysis values [7,18,21,22]. Seven patients (1%) developed hyponatraemia with no clinical symptoms [21,22].…”
Section: Efficacy Of Long‐term Desmopressin Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Headaches were reported in four children (of a total of 689) and stomach ache in three. Even during long-term treatment with desmopressin, side-effects are rarely reported [19,48,49]. However, there are rare reported cases of hyponatraemia with desmopressin treatment [50].…”
Section: Acceptability Of Treatmentmentioning
confidence: 99%